PERANAN KEPEMIMPINAN DALAM PEMBERDAYAAN PEGAWAI PADA KANTOR BAGIAN PERTANAHAN SEKRETARIAT DAERAH KABUPATEN LAHAT - Yulia Hartati (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2022)
This Research aim to to test How Role Leadership In Enableness of Officer At Part Of Land Secretariat Area Sub-Province Lahat. Technique Intake of sampel weared by is census method conducted by taking the overall of subyek, sampel in this research amount to Thirty One who is in Part Of Land Secretariat Area Sub-Province Lahat. Analysis Data at this research use deciphrable descriptive method qualitative as trouble-shooting investigated with mengambarkan situation of object or subjek research of someone, institute, society etc. at the time of now pursuant to fact which look or as it is. From result of research obtained that role of leadership in course of enableness have walked eminently able to be seen from existence of system execution location of officer, officer development, conservancy of officer exploiting and officer. Leadership at Part Of Land Secretariat Area SubProvince Lahat have succeeded to execute enableness of officer effectively. This matter is proved with existence of system location of officer pursuant to objective criterion, executed officer development system intensively and pay attention ability of officer and also officer exploiting system paying attention psychology condition and requirement all its officer